The humanization and the clown: between meanings and smiles (Research, Society and Development, 2022)
Humanization is inserted in the health field as an essential resource in practices. Within the range of agents that make this process possible, the palazzo stands out as a promoter of humanization. A survey was carried out in a hospital outside the state of Sergipe, where data were collected in 2018, through an interview that was carried out after the interventions of two patients, members of the Território Feliz project. The general objective of the research is to understand the meaning of humanization in the hospital context, for different actors, through the attitude of the patient. Data analysis was performed using the Socio-Historical approach. As a result, I observed that the sense of humanization is intrinsically linked to the field of human relations, involving the understanding of ethics, two values ​​and relationships as a means in which subjects are inserted, and these two great obstacles to humanization Place, place. the singularity of two subjects and their potential as health promoters occur without exclusion. In this sense, it highlights the urgency of inserting humanization in hospital environments, where relationships are fragile, distant and permeated by the logic of work, engendered by practices and technical actions whose only purpose is care.